SOLUBILITY ENHANCEMENT OF GLIBENCLAMIDE USING MESOPOROUS SILICA - Mittal, Swati; AKSHAY SONAWANE; MANGESH KHUNE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Glibenclamide is a BCS Class II drug and poses a major problem during formulation development. In the present study, adsorption onto various carriers was used to enhance the solubility of glibenclamide. It was observed that solubility of glibenclamide was greatly enhanced by adsorbing onto mesoporous silica. The increase in solubility of poorly soluble drugs is often associated with the generation of supersaturation, which results in the risk of drug precipitation. HPMC E5 was used as precipitation inhibitor to maintain sink condition for a longer duration. A 32 full factorial design was adopted to optimize the ratio of glibenclamide (X1) and mesoporous silica as a carrier (X2) and the effect of different ratios was studied on percent yield, percent drug loading, and percent drug release. X-ray powder diffraction (XRPD) and Differential scanning calorimetry studies were performed to investigate any possible interaction in between glibenclamide and mesoporous silica. An optimum batch of drug adsorbate was used to prepare immediate-release tablets. The tablets prepared were evaluated for thickness, uniformity of weight, hardness, friability, in-vitro disintegration time, and in vitro drug release study.